Designing Business Intelligence Dashboards to Support Decision-Making in a Fishery Business - Raihanto, Muhammad Satya; Febrianti, Melinska Ayu; Qurtubi, Qurtubi; Setiawan, Danang; Auliana, Windi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Accurate assessment and thorough analysis of managerial performance are essential in obtaining enhanced business performance. A real-time monitoring system is necessary to support the decision-making process. This study aims to design a business intelligence dashboard containing real-time monitoring of water quality to support the decision-making of the management team of an agribusiness company. Four steps were used in designing the business intelligence (BI) dashboard: (1) scope and plan, (2) analyze and define, (3) architect and design, and (4) build, test, and refine. The study started with determining the scope and plan for developing the BI dashboard to monitor the water pond’s quality in real time. The requirements of system input and output were identified in the analyze and define phase. The data warehouse model and design visualization regarding the BI dashboard were determined in the architect and design step. The system's architecture was analyzed in the final step, build and test. Three months of data collection and interviews with the management team of the fishery company were performed to support each step in BI design. This study’s outcome is a BI dashboard providing real-time monitoring that supports the management team's decision-making process. This study still considers two water quality measures; therefore, future research can be conducted using other measures. Future research can also be performed on another agribusiness company to support the decision-making process and increase competitiveness.